1985
DOI: 10.1111/j.1365-2133.1985.tb04863.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical sodium cromoglycate in the management of atopic eczema—a controlled trial

Abstract: A double-blind, group comparison trial of a topical cream containing 4% sodium cromoglycate (SCG) was undertaken in forty-six patients with chronic atopic eczema. A statistically significant improvement was seen after 9 weeks in the actively treated patients compared with the placebo group. However, in general, no benefit was observed in severe eczema, perhaps due in some part to the seemingly late onset of action of SCG. Measurement of total serum IgE before and after the trial showed an increase in levels wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…One possible explanation is the poor and inconsistent penetration of cromones into the skin. Given their polar nature (p K a ∼2), penetration of these drugs through the epidermis with conventional vehicles is very poor, one study reporting a mean efficiency of absorption of 0.44% (range 0.01 – 2.75%) from an oil in water formulation containing 4% sodium cromoglycate ( Ariyanayagam et al ., 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is the poor and inconsistent penetration of cromones into the skin. Given their polar nature (p K a ∼2), penetration of these drugs through the epidermis with conventional vehicles is very poor, one study reporting a mean efficiency of absorption of 0.44% (range 0.01 – 2.75%) from an oil in water formulation containing 4% sodium cromoglycate ( Ariyanayagam et al ., 1985 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Clinical studies of mast cell degranulation inhibition in AD patients have produced divergent results with both improvement of the eczema seen in some, 5,6 but not all studies. 7,8 However, mast cell density has not been shown to correlate with severity of AD, 9 and plasma levels of mast cell mediators in AD have been found to be normal. 10 There is also some controversy about the role of histamine in AD patients.…”
mentioning
confidence: 99%
“…Several authors describe an increased density of mast cells in AD 1,2 and speculate on the pathophysiological relevance of mast cells in AD 3,4 . Clinical studies of mast cell degranulation inhibition in AD patients have produced divergent results with both improvement of the eczema seen in some, 5,6 but not all studies 7,8 . However, mast cell density has not been shown to correlate with severity of AD, 9 and plasma levels of mast cell mediators in AD have been found to be normal.…”
mentioning
confidence: 99%
“…Two further trials used this formulation, 17,18 but neither showed any clear benefits. Three trials used a 4% oil‐in‐water cream formulation 19–21 and only one of these 21 showed positive effects. In three trials carried out in Japan the drug was applied to the skin as a 1% aqueous solution 5–7 .…”
Section: Discussionmentioning
confidence: 99%